Selection of legitimate dwarf coconut hybrid seedlings using DNA fingerprinting - Azevedo,Alinne Oliveira Nunes (2018)
Abstract Due to the great economic importance of coconut palm in Brazil and the development of a coconut breeding program intended to produce intravarietal hybrids, the present work aimed to ease the production of hybrids with the same morphological heritage. DNA was extracted from leaf samples of 13 dwarf coconut populations from Brazil, and PCR amplification was performed using 21 previously selected microsatellites. Furthermore, this study selected nine microsatellite markers with the potential to identify Green Dwarf x Yellow Dwarf hybrids and 16 microsatellites with the potential to identify Red Dwarf x Yellow Dwarf hybrids. In conclusion, SSR marker based on DNA Fingerprinting allowed the accurate identification of legitimate intravarietal hybrids since, for those crosses, the methodology of identification based on seedling color is not a viable alternative.